The hero with a thousand faces - Campbell, Joseph (Meridian books, M22, 1993)
A study of heroism in the myths of the world - an exploration of all the elements common to the great stories that have helped people make sense of their lives from the earliest times. It takes in Greek Apollo, Maori and Jewish rites, the Buddha, Wotan, and the bothers Grimm's Frog-King.